2018
DOI: 10.1177/0363546518765479
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment With Closing-Wedge Distal Femoral Osteotomy for Recurrent Patellar Dislocation With Genu Valgum

Abstract: CWDFO combined with medial reefing and lateral release successfully treated RPD with genu valgum for a minimum follow-up of 2 years, with improved patellar alignment and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 35 publications
3
95
1
2
Order By: Relevance
“…This is because the valgus moment to the patella is reduced by decreasing the Q angle, and the congruity of the patella is thus Table 4 Results of patellofemoral joint congruity improved. However, these results deviate from our study, which showed that there is no effect on the patellar tilt or shift because combined procedures were proactively performed with DFO for patellar instability to improve patellar tracking, including tibial tuberosity osteotomy [23,26], medial reefing [23,25,26] and lateral release [23,26,27]. In our study, the mean preoperative tilt and shift were small at 5.1°and 6.8%, respectively, and there were no cases with patellar instability.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This is because the valgus moment to the patella is reduced by decreasing the Q angle, and the congruity of the patella is thus Table 4 Results of patellofemoral joint congruity improved. However, these results deviate from our study, which showed that there is no effect on the patellar tilt or shift because combined procedures were proactively performed with DFO for patellar instability to improve patellar tracking, including tibial tuberosity osteotomy [23,26], medial reefing [23,25,26] and lateral release [23,26,27]. In our study, the mean preoperative tilt and shift were small at 5.1°and 6.8%, respectively, and there were no cases with patellar instability.…”
Section: Discussioncontrasting
confidence: 88%
“…In terms of DFO performed to correct valgus deformity in knees with patellar instability, several studies have examined the postoperative change in patellar height; however, the results have been inconsistent between studies. Nha et al [23] reported that there was no significant postoperative change in patellar height as assessed by the Caton-Deschamps index in knees that underwent medial closed DFO for patellar dislocation associated with valgus knee deformity. On the other hand, Wilson et al [24] reported a significant reduction in the Caton-Deschamps index following lateral open DFO performed for recurrent patellar instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patellar height was measured using the method applied by Insall [12]. The patellar lateral shift (PLS) was calculated by CT at 30 degrees of knee exion, as described by Nha et al [11], and was de ned as the shortest distance from the cortex of the lateral trochlea to the lateral edge of the patella. The pro le information of these patients are presented in Table 1.…”
Section: Clinical and Radiological Evaluationmentioning
confidence: 99%
“…In terms of patellar instability, the popularly accepted opinion is the MPFLR [10]. However, patellar maltracking could be restored by DFO in the patients with genu valgum [11]. So, CWDFO combined MPFLR could be justi ed in these patients with genu valgum.…”
Section: Introductionmentioning
confidence: 99%